A probability distribution model of tooth pits for evaluating time-varying mesh stiffness of pitting gears. (June 2018) - Lei, Yaguo; Liu, Zongyao; Wang, Delong; Yang, Xiao; Liu, Huan; Lin, Jing
Highlights: A probability distribution model describing tooth pitting of spur gears is proposed. The locations of pits are modeled as a two-dimensional random variable. Pits are modeled with gradually increased sizes instead of fixed ones. Mesh stiffness under four pitting degrees from no pitting to severe pitting is evaluated. Abstract: Tooth damage often causes a reduction in gear mesh stiffness. Thus time-varying mesh stiffness (TVMS) can be treated as an indication of gear health conditions. This study is devoted to investigating the mesh stiffness variations of a pair of external spur gears with tooth pitting, and proposes a new model for describing tooth pitting based on probability distribution. In the model, considering the appearance and development process of tooth pitting, we model the pitting on the surface of spur gear teeth as a series of pits with a uniform distribution in the direction of tooth width and a normal distribution in the direction of tooth height, respectively. In addition, four pitting degrees, from no pitting to severe pitting, are modeled. Finally, influences of tooth pitting on TVMS are analyzed in details and the proposed model is validated by comparing with a finite element model. The comparison results show that the proposed model is effective for the TVMS evaluations of pitting gears.